2017
DOI: 10.1016/j.cllc.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Late-Stage Non–Small-Cell Lung Cancer Cachexia on Muscle Metabolic Processes

Abstract: The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 54 publications
1
31
0
Order By: Relevance
“…Somatic mutations in the DDR2 kinase gene were also indicated as the potential targets for the treatment of a portion of patients with LSCC ( 20 , 22 ). These results reflected the heterogeneity of human tumor types ( 23 ), and explain the large size of the LSCC risk gene pool curated through previous studies ( 4 12 ).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Somatic mutations in the DDR2 kinase gene were also indicated as the potential targets for the treatment of a portion of patients with LSCC ( 20 , 22 ). These results reflected the heterogeneity of human tumor types ( 23 ), and explain the large size of the LSCC risk gene pool curated through previous studies ( 4 12 ).…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, there are numerous novel genes identified each year for LSCC. For example, in 2017, fibroblast growth factor receptor (FGFR) 4 and microRNA 145 were novelly reported as LSCC risk genes that serve roles in the mechanism of the disease ( 11 , 12 ). These genes have been identified in limited LSCC studies, which may be due to the specificity of genome variations in different patients ( 13 ); therefore, early diagnosis/prediction of LSCC may require multiple genes as biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies as well as the current study show that sarcopenia is heavily correlated with cancer stage and treatment; yet across all strata of treatment and cancer stage, patients with sarcopenia perform worse [41, 42]. This indicates that, regardless of cancer stage and treatment, sarcopenia is an independent predictor of outcome.…”
Section: Discussionmentioning
confidence: 49%
“…For the exploratory analysis of genes associated with obesity and lung cancer survival we further analyzed the association between obesity genes (LEP, LEPR, PCSK1, POMC, MC4R, BMIQ1, BMIQ2, BMIQ3, UCP2, BMIQ5, BMIQ6, INSIG2, FTO, TMEM18, GNPDA2, NEGR1, BDNF, KCTD15, SH2B1, MTCH2 and NPC1) 9 and lung cancer survival from a separate Cancer Genome Atlas data set (TCGA). The TCGA is an independent and centralized database with genomic and genetic profiles of various cancer patients, including lung cancer.…”
Section: Resultsmentioning
confidence: 99%
“…A small study by Murton et al found lung cancer cachexia patients with high mRNA levels of interleukin 6 and low intramyocellular lipid content in slow twitch fibers. 9 Fukawa et al studied fatty acid oxidation and muscle atrophy in cancer related cachexia in vitro and in vivo . 10 They found cachectic cancer cells secret inflammatory factors and rapidly induce excessive fatty acid oxidation in myotubules, which causes oxidative stress and muscle atrophy.…”
Section: Discussionmentioning
confidence: 99%